The First Sail: J. Hillis Miller - Kujundžić, Dragan (Open Humanities Press, 2015)
The film-book The First Sail: J. Hillis Miller is based on the documentary film of the same name made in 2010. The political, academic and environmental contexts surrounding this film since its release prove with more and more urgency the need to read and listen to J. Hillis Miller, and would require revisiting everything that has been said and seen. Together with the film transcript and an interview with Miller conducted by Taryn Devereux, the essays in this volume have been gathered from several international events devoted to Miller's works. With essays by Henry Sussman, Sarah Dillon, Charlie Gere, Nicholas Royle, Éamonn Dunne and Michael O'Rourke, Dragan Kujundžić, Julian Wolfreys and J. Hillis Miller, The First Sail in itself thus forms a vast network of references, operating as an installation and network of emerging projects.